The Emergence of the Open Research University Through International Research Collaboration - Heiser, Rebecca E. (International Review of Research in Open and Distributed Learning, 2023)
In higher education, international research collaboration functions as a visible mechanism of cooperation and competition, serving as a proxy for quality and academic excellence. Open universities use revolutionary education models but are not often associated with quality or academic excellence. To investigate the impact of international research collaboration by active researchers affiliated with open institutions, a bibliometrics analysis was conducted of three open universities and nine traditional, comparative universities between 2000 and 2022. The results indicate that research outputs that are open access, sponsored and funded, and developed with international coauthors have positive and statistically significant effects on citation counts. Moreover, international research collaboration significantly affects all universities, not just open institutions. The results conclude that researchers affiliated with open universities are only 4.3% less cited than their comparative peers, which is attributed to publication factors, research disciplines and subject areas, and journal characteristics. Findings are discussed and imply a strategic shift in the institutional functions and outputs of open universities as collaborative conduits of knowledge production and dissemination.